ANALISIS KESULITAN SISWA DALAM MENYELESAIKAN SOAL BERBASIS HOTS (HIGHER ORDER THINKING SKILL) KELAS IV SEKOLAH DASAR - Doni Adi; Muhammad Makki; Setiani Novitasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to describe the difficulties faced by students in solving HOTS-based (Higher Order Thinking Skills) questions in Social Studies subjects for fourth-grade elementary school students. This research employed a descriptive qualitative approach. The subjects of this study were 11 fourth-grade students at SDN 3 Brang Rea. Data collection techniques included tests and interviews. The test instrument consisted of 10 multiple-choice questions based on HOTS principles aligned with the Social Studies curriculum. Data were analyzed using the Miles and Huberman model, which involves data reduction, data display, and conclusion drawing. The results indicated that students experienced various difficulties in solving HOTS questions, including challenges in understanding the intent of the questions, connecting the information in the questions with their prior knowledge, reading long questions, formulating reasons or solutions, and maintaining concentration during the test. In addition, interview findings revealed other contributing factors, such as low reading interest, dependence on external help, and lack of independent practice. These findings highlight the need for instructional strategies that develop higher-order thinking skills in a gradual, contextual, and holistic manner.